2015
DOI: 10.3168/jds.2015-9710
|View full text |Cite
|
Sign up to set email alerts
|

Tocopherols and tocotrienols in serum and liver of dairy cows receiving conjugated linoleic acids or a control fat supplement during early lactation

Abstract: The fat-soluble vitamin E comprises the 8 structurally related compounds (congeners) α-, β-, γ-, and δ-tocopherol (with a saturated side chain) and α-, β-, γ-, and δ-tocotrienol (with a 3-fold unsaturated side chain). Little is known regarding the blood and liver concentrations of the 8 vitamin E congeners during the transition from pregnancy to lactation in dairy cows. We thus quantified tocopherols (T) and tocotrienols (T3) in serum and liver and hepatic expression of genes involved in vitamin E metabolism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…β-Carotene may support the antioxidative effect of tocopherol in a synergistic manner (Palozza and Krinsky, 1992). However, CLA treatment in previous studies failed to influence plasma tocopherol concentrations in dairy cows (Sadri et al, 2015;Hanschke et al, 2016) but increased tocopherol concentration in milk (Gessner et al, 2015).…”
Section: Effects Of Fa Supplementation On Systemic and Hepatic Inflammatory And Antioxidative Statusmentioning
confidence: 85%
“…β-Carotene may support the antioxidative effect of tocopherol in a synergistic manner (Palozza and Krinsky, 1992). However, CLA treatment in previous studies failed to influence plasma tocopherol concentrations in dairy cows (Sadri et al, 2015;Hanschke et al, 2016) but increased tocopherol concentration in milk (Gessner et al, 2015).…”
Section: Effects Of Fa Supplementation On Systemic and Hepatic Inflammatory And Antioxidative Statusmentioning
confidence: 85%
“…The preparation of the samples, including RNA extraction and cDNA synthesis, was described in detail previously (Saremi et al, 2012a,b;Sadri et al, 2015). Quantification of the mRNA of the targeted genes was performed in an Mx3000P cycler (Agilent, Santa Clara, CA) and in accordance with MIQE guidelines (Bustin et al, 2009).…”
Section: Rna Extraction and Quantitative Real-time Reverse Transcriptmentioning
confidence: 99%
“…Jensen et al [54] showed that after a single dose injection of all-rac-α-tocopheryl acetate, the RRR-α-Toc was retained in plasma for the longest time and secreted into milk at the highest concentration followed by RRS-, RSS-, and RSRα-Toc leaving the Σ2S-α-Toc to be retained in plasma for the shortest time and secreted into milk at the lowest concentration. In dairy cows during early lactation, the serum concentrations (nM) of γ-Toc, α-, β-, γand δ-tocotrienol were far lower than those of α-Toc (approximately 1/56, 1/214, 1/3947, 1/5000 and 1/2500, respectively) [55]. Among the naturally occurring forms of the VE family, α-Toc only meets VE requirements and α-Toc stereoisomers have different bioactivities because α-Toc transfer protein (αTTP) has a different affinity for VE (described in Section 2.2.1) and play an important role in the circulation and disposition of α-Toc in cattle.…”
Section: Vitamin E (α-Tocopherol)mentioning
confidence: 89%